2015
DOI: 10.32674/jis.v5i4.401
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Motivations, Expectations, and Experiences of Students Who Study in Global Settings

Abstract: An increasing trend of universities is to provide students with opportunities to engage in global learning experiences (GLE) as part of their program of study. While there are numerous papers on the benefits of international and study abroad programs, there is little research on factors that impact GLE. This study evaluated the student perspective through qualitative and quantitative responses to surveys and questions posed during a period of three years. The results suggested that students’ motivation and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Cross-cultural experience and academics motivational factors are tied into students' expectations of summer abroad program. They include foreign language acquisition, exposure and immersion into foreign cultures, independence and unique experiences (Badstübner and Ecke, 2009;Nguyen and Coryell, 2015;Pope et al, 2014;Salyers et al, 2015). Cultural values motivation was researched by Schwartz et al (2009).…”
Section: Cross-cultural Experiencesmentioning
confidence: 99%
“…Cross-cultural experience and academics motivational factors are tied into students' expectations of summer abroad program. They include foreign language acquisition, exposure and immersion into foreign cultures, independence and unique experiences (Badstübner and Ecke, 2009;Nguyen and Coryell, 2015;Pope et al, 2014;Salyers et al, 2015). Cultural values motivation was researched by Schwartz et al (2009).…”
Section: Cross-cultural Experiencesmentioning
confidence: 99%
“…These orientations require experts who are aware of the host country. Experts can design relevant activities aimed at building group cohesion and addressing students' safety and health concerns, thereby reducing anxiety among students (Salyers et al, 2015). All these activities characterize the predeparture orientations of the service-learning program in Uganda, where both faculty and staff from MAK and ISU, ISU-UP staff, service-learning alumni, healthcare providers, and cultural leaders in Uganda are involved in orientations that break the fear of the unknown.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…This study includes additional inputs representing important situational factors found in the study abroad literature. Students who receive academic financial aid are less burdened by financial constraints that might deter them from studying abroad (Bell et al , 2022; Salyers et al , 2015). The workflow management of this university collects financial aid information for each student who inquires about a study away program.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have examined negative pressures that work to lower student intentions to study abroad despite the many perceived benefits. Students often face situational constraints such as financial limitations or family responsibilities that preclude them from participating (Salyers et al , 2015). Program costs are especially discouraging to first-generation students and those with lower socioeconomic backgrounds (Lehmann, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%